Z-Small Quasi-Dedekind Modules - Shyaa, Farhan Dakhil; Al-Sada, Hawraa Abd (Iraqi Journal of Science, 2023)
In this paper, we define and study z-small quasi-Dedekind as a generalization of small quasi-Dedekind modules. A submodule of -module is called z-small ( if whenever , then . Also, is called a z-small quasi-Dedekind module if for all implies . We also describe some of their properties and characterizations. Finally, some examples are given.